Mental Health in COVID-19 Pandemic: A Meta-Review of Prevalence Meta-Analyses - Sousa, Geovan Menezes de; Tavares, Vagner Deuel de Oliveira; de Meiroz Grilo, Maria Lara Porpino; Coelho, Monique Leite Galvão; Lima-Araújo, Geissy Lainny de; Schuch, Felipe Barreto; Galvão-Coelho, Nicole Leite (Frontiers in Psychology, 2021)
Background: Mental health burden has been massively reported along the COVID-19 pandemic. Aiming to summarize these data, we present a meta-review of meta-analyses that evaluated the impact of COVID-19 pandemic on anxiety, depressive and stress symptoms, psychological distress, PTSD, and sleep disturbance, reporting its prevalence on general public (GP) and healthcare workers (HCW). Methods: Search was performed in PubMed, EMBASE, and Web of Science. Sleep disturbances, psychological distress, stress, and burnout were grouped as “Psychophysiological stress”, and anxiety, depression and PTSD were grouped as “Psychopathology”. A random-effects model, calculating the pooled prevalence together with 95% confidence interval, was performed for each domain. Subgroup analyses were performed for each population type (GP and HCW) and for each mental health outcome. For anxiety and depression, subgroup analysis for population type was performed. Heterogeneity is reported as I2. Publication bias was assessed through visual inspection of the funnel plot, and further tested by Egger's test and trim and fill analyses. Results: A total of 18 meta-analyses were included. The prevalence of psychophysiological stress was 31.99% (CI: 26.88-37.58, I2 = 99.9%). HCW showed a higher prevalence (37.74%, CI: 33.26-42.45, I2 = 99.7%) than the GP (20.67%, 15.07-27.66, I2 = 99.9%). The overall prevalence of insomnia, psychological distress, and stress were, respectively 32.34% (CI: 25.65-39.84), 28.25% (CI: 18.12-41.20), and 36% (CI: 29.31-43.54). Psychopathology was present at 26.45% (CI: 24.22-28.79, I2 = 99.9%) of the sample, with similar estimates for population (HCW 26.14%, CI: 23.37-29.12, I2 = 99.9%; GP: 26.99%, CI: 23.41-30.9, I2 = 99.9%). Anxiety, depression, and PTSD prevalences were 27.77% (CI: 24.47-31.32), 26.93% (CI: 23.92-30.17), and 20% (CI: 15.54-24.37), respectively. Similar proportions between populations were found for anxiety (HCW = 27.5%, CI: 23.78-31.55; GP = 28.33%, CI: 22.1-35.5) and depression (HCW = 27.05%, CI: 23.14-31.36; GP = 26.7%, CI: 22.32-31.59). Asymmetry in the funnel plot was found, and a slightly increase in the estimate of overall Psychopathology (29.08%, CI: 26.42-31.89) was found after the trim and fill analysis. Conclusions: The prevalence of mental health problems ranged from 20% to 36%. Healthcare workers presented a higher prevalence of psychophysiological stress than the general population.